STAT3 and p63 in the Regulation of Cancer Stemness - Wei, Shixiong; Li, Jialin; Tang, Mingbo; Zhang, Kewei; Gao, Xinliang; Fang, Linan; Liu, Wei (Frontiers in Genetics, 2022)
Signal Transducer and Activator of Transcription 3 (STAT3) is a transcription factor with many important functions in normal and transformed cells. STAT3 regulatory activities are highly complex as they are involved in various signaling pathways in different cell types under different conditions. Biologically, STAT3 is a regulative factor for normal and cancer stem cells (CSCs). Tumor protein p63 (p63), a member of the p53 protein family, is involved in these biological processes and is also physically and functionally associated with STAT3. STAT3 activation occurs during various aspects of carcinogenesis, including regulation of CSCs properties. In combination with p63, STAT3 is a possible biological marker of CSCs and a major regulator of maintenance of stemness in CSCs. We summarized the STAT3 functions and regulation, its role in CSCs properties and highlight how these are affected by its associations with p63.